LEARNING OUTCOMES AT THE COGNITIVE LEVEL OF UNDERSTANDING (C2): HOW EFFECTIVE IS THE SAVI LEARNING MODEL IN AKIDAH AKHLAK INSTRUCTION? - Dea Asmara; Agus Pahrudin; Riyan Terna Kuswanto; Baharudin (QANUN: Journal of Islamic Laws and Studies, 2025)
This study aims to examine the effect of the Somatic, Auditory, Visual, and Intellectual (SAVI) learning model on students’ learning outcomes in the Akidah Akhlak subject, specifically at the cognitive level C2 (understanding). The research is motivated by the low level of students’ conceptual comprehension, which is largely attributed to teacher-centered instruction and limited multisensory engagement in the learning process. A quantitative approach was employed using a quasi-experimental design, namely a post-test–only control group design. The sample consisted of two eighth-grade classes at MTs Ma’arif 31 Tribhakti: an experimental class that implemented the SAVI model and a control class that received conventional instruction. Data were collected using a C2-level learning outcome test and analyzed through normality testing, homogeneity testing, and an independent samples t-test.The results demonstrate that the SAVI learning model has a significant effect on improving students’ learning outcomes. The t-test findings indicate a statistically significant difference between the experimental and control groups, confirming that the SAVI model effectively enhances students’ understanding of Akidah Akhlak material. This improvement is attributed to the model’s integration of multisensory activities that support deeper comprehension and facilitate the internalization of moral values.The novelty of this research lies in its focused application of the SAVI model to strengthen C2-level understanding in Akidah Akhlak, a topic that has received limited scholarly attention. The study highlights that the SAVI model is particularly effective in clarifying abstract concepts and fostering meaningful learning experiences. The implications suggest that SAVI can serve as an innovative instructional alternative for teachers, enabling more active, engaging, and student-centered learning that ultimately contributes to enhancing the overall quality of Akidah Akhlak education.